Aristotelian political philosophy and its implications for contemporary Ghana - Isaac Boaheng (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
No human society if free from socio-political challenges. However, developing countries tend to face more challenges than developed ones. Ghana is West-African country that faces a lot of socio-political challenges such as poverty, poor infrastructure, local currency depreciation, high inflation, corruption, and high unemployment rate, among others. This paper used a literature-based research approach to explore what political lessons Ghana can learn from the political philosophy of Aristotle. The study draws political lessons for Ghana based on three thematic areas; namely, the reality of diversity and the need for political inclusiveness, the need for educational reforms and community-mindedness of the citizenry. The main thesis of the paper is that political activities must be geared toward the wellbeing of the society rather than the selfish interest of political actors. The paper serves as a foundation upon which a more detailed and comprehensive political theology could be formulated for Ghana and Africa at large